SYNTAXONOMY OF SUBALPINE TALL-GRASS COMMUNITIES (CALAMAGROSTIETALIA VILLOSAE) IN THE UKRAINIAN DISTRICTS OF EASTERN CARPATHIANS - D. Iakushenko (Annali di Botanica, 2012)
This paper presents a phytosociological survey of subalpine tall-grass communities within the order Calamagrostietalia villosae (class Mulgedio-Aconitetea) in the Ukrainian districts of the Eastern Carpathians. This  syntaxonomical revision includes relevés from  the mountain ranges Beskydy, Gorgany, Chornohora, Svydovets’, Marmarosh, Hryniava, and Chyvchyny. The analysis was performed using numerical classification methods. Five associations within three alliances were distinguished and concisely characterized. Typification and name inversion of the association Hyperico alpigeni-Calamagrostietum villosae Pawłowski et Walas 1949 nom. invers. propos. was performed.